Meteorological, PM2.5 and PM10 factors on SARS-COV-2 transmission: The case of southern regions in Chile. (1st April 2023) - Scapini, Valeria; Torres, Soledad; Rubilar-Torrealba, Rolando
Abstract: There are several determinants of a population's health, including meteorological factors and air pollution. For example, it is well known that low temperatures and air pollution increase mortality rates in infant and elderly populations. With the emergence of SARS-COV-2, it is important to understand what factors contribute to its mitigation and control. There is some research in this area which shows scientific evidence on the virus's behavior in the face of these variables. This research aims to quantify the impact of climatic factors and environmental pollution on SARS-COV-2 specifically the effect on the number of new infections in different areas of Chile. At the local level, historical information available from the Department of Statistics and Health Information, the Chilean National Air Quality Information System, the Chilean Meteorological Directorate, and other databases will allow the generation of panel data suitable for the analysis. The results show the significant effect of pollution and climate variables measured in lags and will allow us to explain the behavior of the pandemic by identifying the relevant factors affecting health, using heteroskedastic models, which in turn will serve as a contribution to the generation of more effective and timely public policies for the control of the pandemic. Graphical abstract: Highlights: The contributions of this work are the following: SARS-COV-2 is linked to temperature and particulate matter in southern Chile. Heteroskedastic models estimates climate and particulate matter factors on SARS-COV-2. The lagged climatic and particulate matter variables impact on SARS-COV-2.